Endoscopic detachable snare ligation: a new treatment method for colonic diverticular hemorrhage - Akutsu, Daisuke; Narasaka, Toshiaki; Wakayama, Mariko; Terasaki, Masahiko; Kaneko, Tsuyoshi; Matsui, Hirofumi; Suzuki, Hideo; Hyodo, Ichinosuke; Mizokami, Yuji (Endoscopy, 2015)
Background and study aims: Colonic diverticular hemorrhage is the most common cause of lower intestinal bleeding. We tried to develop a convenient and reliable hemostatic method, endoscopic detachable snare ligation (EDSL), to treat diverticular hemorrhage and retrospectively explored its safety and efficacy.Patients and methods: The definitive bleeding diverticulum was ligated with a detachable snare, instead of a rubber band, in a procedure similar to endoscopic band ligation. Removal of the scope to attach a ligation device and reinsertion for treatment are not needed in this method.Results: From November 2013 to September 2014, EDSL was used to treat 8 patients with colonic diverticular hemorrhage. The mean procedure time required for hemostasis after identification of the bleeding diverticulum was 5 ± 2 minutes. Sustained hemostasis was achieved in 7 patients (88 %), and early rebleeding occurred in 1 patient, in whom the applied suction seemed inadequate. No complications occurred in any patient.Conclusions: EDSL may be a safe and effective treatment for colonic diverticular hemorrhage. However, additional studies are warranted to confirm these initial exploratory data.